IMPLEMENTASI PENGELOLAAN KEUANGAN DENGAN TRANSAKSI NON TUNAI DI SEKRETARIAT DAERAH PROVINSI SUMATERA BARAT - Husna Rahma Dona; Afriva Khaidir (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
This study tried to explain the implementation of non-cash financial management at the Local Government Secretariat (Sekda) of West Sumatera, the obstacles that arise during implementation and the efforts to overcome these obstacles. This research was motivated by the presence of Surat Edaran Menteri Dalam Negeri Number 910/1866/SJ, dated April 17, 2017 concerning Non-Cash Implementation in Provincial Governments, in each Regional Government in all provinces in Indonesia is required to implement a non-cash transaction system in regional financial management. This research is descriptive with a qualitative approach. The indicator used in this study is accountability, transparency and value of money. Research informants were determined by purposive sampling. The results showed that implementation of financial management of non-cash at the Local Government Secretariat (Sekda) of West Sumatera, had begun in September 2017. The implementation of this online-based non- cash transaction required a structured mechanism and flow for the implementation of the Standard Operating Procedure. But in its implementation, there are various obstacles that arise such as treasurers who have not all followed the flow in the SOP, applications that are still often errors, and the treasurer workload is increasing.